2006
DOI: 10.1248/cpb.54.58
|View full text |Cite
|
Sign up to set email alerts
|

Optically Active Cyclohexene Derivative as a New Antisepsis Agent: An Efficient Synthesis of Ethyl (6R)-6-[N-(2-Chloro-4-fluorophenyl)sulfamoyl]cyclohex-1-ene-1-carboxylate (TAK-242)

Abstract: Sepsis and septic shock remain the chief causes of death in intensive care units, with mortality rates between 30 and 70%.1-3) Although several drug candidates have entered clinical trials over the last 20 years, most have not demonstrated significant benefit for patients with sepsis and septic shock, and difficulties of the development of an antisepsis agent has been proven. In 2001, Drotrecogin-a (Xigris TM ), 4) a recombinant human activated protein C, was launched onto the market as the first antisepsis ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 19 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…1A)} was synthesized using a procedure based on a previous report38, at laboratory of Pharmaceutical and Medicinal Chemistry, Department of Organic and Medicinal Chemistry, Gifu Pharmaceutical University. The compound was identified by 1H-NMR and Mass spectra (see Supplementary Information.)…”
Section: Methodsmentioning
confidence: 99%
“…1A)} was synthesized using a procedure based on a previous report38, at laboratory of Pharmaceutical and Medicinal Chemistry, Department of Organic and Medicinal Chemistry, Gifu Pharmaceutical University. The compound was identified by 1H-NMR and Mass spectra (see Supplementary Information.)…”
Section: Methodsmentioning
confidence: 99%
“…TAK-242 (resatorvid), a small-molecule specific inhibitor of TLR4 signaling, inhibits the production of lipopolysaccharide (LPS)-induced inflammatory mediators by binding to the intracellular domain TIRAP of TLR4 9 . As a result, it completely prevents NF-κB DNA binding, and accordingly represses expression of IL-1β, IL-6, TNF-α, MIP-2 and CCL2 10 . In phase III clinical trials, TAK-242 has demonstrated promising efficacy as an antisepsis agent 11 , 12 .…”
Section: Introductionmentioning
confidence: 99%
“…TAK 242 (resatorvid) is a specific TLR4 inhibitor that has potent anti-inflammatory activity in a variety of inflammatory diseases [ 20 , 21 , 22 , 23 , 24 , 25 ], including endotoxemia-induced skeletal muscle wasting [ 37 ], sepsis [ 20 , 22 , 24 , 38 ], acute kidney injury [ 39 ], neuroinflammation [ 40 ], acute cerebral ischemia [ 41 ], cancer [ 42 ], and rheumatoid arthritis [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The binding of LPS to TLR4 leads to the activation of a series of downstream signaling pathways, which play a fundamental role in various physiological processes [ 18 , 19 ]. TAK 242 (resatorvid) is a TLR4 inhibitor [ 20 , 21 , 22 , 23 , 24 , 25 ], which can suppress a series of cytological events in inflammation, including inflammatory cytokine production, inflammatory gene expression, and inflammation-related pathways activation [ 20 , 23 ]. However, to the best of our knowledge, the effect of TLR4 (Toll-like receptor 4) inhibitor on the transcriptomics of LPS-mediated mouse peritonitis has not been reported yet.…”
Section: Introductionmentioning
confidence: 99%